THE ANTIMYCOBACTERIAL POTENTIAL OF SAMBILOTO (Andrographis paniculata Nees) EXTRACT AGAINST Mycobacterium tuberculosis H37Rv WITH Microscopic-Observation AND Drug-Susceptibility (MODS) METHODE - Asarini; Syamsudin Abdillah; Yulvian Sani; Gemini Alam (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Andrographis paniculata, commonly known as sambiloto, is empirically used for various treatments, including its ability to inhibit the growth of Mycobacterium tuberculosis (M. tuberculosis). This study aims to evaluate the growth inhibition activity of M. tuberculosis strain H37Rv using sambiloto herb extract (Andrographis paniculata). The sambiloto extract was prepared using the maceration method. M. tuberculosis was grown on MODS medium, and the toxicity of sambiloto (A. paniculata) was analyzed using pharmacokinetic prediction studies (pkCMS). The results showed that at concentrations of 0.255 mg/ml, 1.275 mg/ml, and 2.55 mg/ml of sambiloto extract, M. tuberculosis growth occurred on days 7 to 14. Further observations were made until day 28, and it was found that starting at a concentration of 6.375 mg/ml, sambiloto extract did not show M. tuberculosis growth in MODS medium. The positive control, isoniazid, did not show bacterial growth, while the negative control showed extensive bacterial growth on day 12. The determination of M. tuberculosis growth was based on microscopic observations of the bacterial colonies, focusing on cord formation. In conclusion, this study, the use of an extract with a concentration of 6.375 mg/ml in the MODS method showed no growth of Mycobacterium tuberculosis, indicating that the extract is effective in inhibiting bacterial growth at this concentration. The online pkCSM test conducted in this study showed that the extract used is not cytotoxic, meaning that the extract is safe for body cells and does not cause cellular damage. Therefore, it has the potential to be an adjunct therapy in the treatment of tuberculosis.